2017
DOI: 10.1007/s10592-017-0999-6
|View full text |Cite
|
Sign up to set email alerts
|

Landscape determinants of genetic differentiation, inbreeding and genetic drift in the hazel dormouse (Muscardinus avellanarius)

Abstract: Landscape determinants of genetic differentiation, inbreeding and genetic drift in the hazel dormouse (Muscardinus avellanarius)Bani, L.; Orioli, V.; Pisa, G.; Dondina, O.; Fagiani, S.; Fabbri, E.; Randi, E.; Mortelliti, A.; Sozio, G. Published in: Conservation Genetics DOI (link to publication from Publisher):10.1007/s10592-017-0999-6 Creative Commons License Unspecified Publication date: 2018 Document VersionPublisher's PDF, also known as Version of record Link to publication from Aalborg University Citation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…Landscape genetics studies can, in turn, inform more targeted management approaches to promote species conservation than those that simply use existing information about habitat preferences (Segelbacher et al 2010). For example, recent studies on a range of taxa, including the hazel dormouse (Muscardinus avellanarius; Bani et al 2017), the alpine newt (Ichthyosaura alpestris; Luqman 2018), and wild tigers (Panthera Electronic supplementary material The online version of this article (https ://doi.org/10.1007/s1059 2-019-01172 -6) contains supplementary material, which is available to authorized users. tigris; Thatte et al 2018) have leveraged landscape genetic results to prioritize conservation goals for these species.…”
Section: Introductionmentioning
confidence: 99%
“…Landscape genetics studies can, in turn, inform more targeted management approaches to promote species conservation than those that simply use existing information about habitat preferences (Segelbacher et al 2010). For example, recent studies on a range of taxa, including the hazel dormouse (Muscardinus avellanarius; Bani et al 2017), the alpine newt (Ichthyosaura alpestris; Luqman 2018), and wild tigers (Panthera Electronic supplementary material The online version of this article (https ://doi.org/10.1007/s1059 2-019-01172 -6) contains supplementary material, which is available to authorized users. tigris; Thatte et al 2018) have leveraged landscape genetic results to prioritize conservation goals for these species.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that R. ornativentris hatchability tends to be low in isolated urban populations (Okamiya & Kusano, ; Shiga, ). A similar phenomenon of fitness reduction due to the erosion of gene flow and genetic diversity in fragmented habitats has been corroborated for several taxa, ranging from invertebrates to mammals (i.e., Bani et al, ; Takahashi et al, ; Unfried et al, ). While results from a single species cannot be generalized for other taxonomic groups, R. ornativentris data are illustrative for other pond‐breeding amphibians such as bufonid toads and small salamanders that inhabit secondary forests surrounded by urbanized areas, because they share many life history traits (Kusano et al, ; Maeda & Matsui, ).…”
Section: Discussionmentioning
confidence: 59%
“…Indeed, the HSu habitat suitability map revealed that a highly urbanized foothill were surrounded by areas with very low suitability and separated by barriers (Figure 2a,b). Thus, anthropic surfaces confine fragmented habitats, hindering dispersal or increasing mortality (Bani et al, 2018;Fahrig, Pedlar, Pope, Taylor, & Wegner, 1995;Shirk, Wallin, Cushman, Rice, & Warheit, 2010). These effects are synergistic and emphasize between-population genetic differences, potentially even reducing genetic diversity (Keller & Largiader, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase of connectivity in fragmented landscapes is essential to restore or improve the genetic exchanges between animal populations, generate new genotypes and increase genetic diversity [57,58,59,60]. This is fundamental to ensure population resilience to future Table 2.…”
Section: Discussionmentioning
confidence: 99%